Early and chronic phased local coagulative responses following bioresorbable-polymer drug-eluting stent implantation. (14th October 2021) - Yamaguchi, K; Wakatsuki, T; Okushi, Y; Suto, K; Matsumoto, K; Takahashi, T; Kadota, M; Kawabata, Y; Matsuura, T; Ise, T; Kusunose, K; Yagi, S; et al.
Abstract: Background: Neointimal maturation after bioresorbable-polymer (BP) drug-eluting stent (DES) implantation will not be complete in the absorption phase of the polymer. We have previously reported local persistent hypercoagulation after sirolimus-eluting stent (SES) implantation by measuring local plasma prothrombin fragment 1+2 (F1+2) levels. The aim of this study is to examine time-dependent local coagulative response after BP-DES implantation. Methods: Sixty-four patients who were treated about ten months earlier with coronary angioplasty, with no evidence of restenosis, were studied [durable-polymer (DP)-DES {SES; Cypher®: 26pts and everolimus-eluting stent (EES); Xience®: 16pts} and BP-DES (BP-EES; Synergy®: 10pts and BP-SES; Ultimaster®: 12pts)]. We measured plasma levels of F1+2 sampled in coronary sinus (CS) and sinus of Valsalva (V) at the early (2±1 months) and chronic (10±2 months) phases. The transcardiac gradient (Δ) was defined as CS level minus V level. Results: No significant differences were observed in the percent diameter stenosis between the DP- and BP- DES groups (11.5±15.5 vs 14.1±11.9%). The ΔF1+2 was significantly lower in the BP-DES group than in the DP-DES group at the chronic phase (7.5±16.1 vs 16.4±17.1pmol/l, p<0.05). In the BP-DES group, the ΔF1+2 did not differ significantly between the early and chronic phases (7.0±14.1 vs 7.5±16.1pmol/l, NS). Conclusion: Lower local coagulative response was observed at the chronic phase after BP-DES implantation compared to DP-DES implantation, and local hypercoagulation after BP-DES implantation was not observed at the early phase compared to the chronic phase. These findings might lead to the possibility of shorter dual antiplatelet therapy after BP-DES implantation. FUNDunding Acknowledgement: Type of funding sources: None.